EL USO DE LA INTELIGENCIA ARTIFICIAL EN LA MANIPULACIÓN DE LA INFORMACIÓN PERIODISTICA - YEPEZ PLAZARTE, LUIGGI GEOVANNY (2024)
The general objective of the research is to analyze the impact of the use of artificial intelligence (AI) in the manipulation of journalistic information. To achieve this objective, a Mixed methodology with a comparative method will be used. Firstly, an exhaustive review of the existing literature on the subject will be carried out to understand the state of the art and trends in the use of AI in the journalistic field, as well as its possible implications in the manipulation of information. This review will allow us to establish a solid theoretical framework based on previous research. Subsequently, in-depth interviews will be carried out with journalists, AI experts and media users to collect qualitative data on their perceptions, experiences and opinions on the topic. Surveys were also developed with students from the Cominication Career of the Technical University of Babahoyo. These interviews and surveys will provide a detailed understanding of how AI is used in journalistic practice and how it can influence the manipulation of information. Finally, the results of both methodological approaches will be integrated to offer robust conclusions and recommendations for journalists, communication professionals and AI developers on how to mitigate the risks of information manipulation in a media environment increasingly dominated by technology.